Fasteners for construction (New Jersey : Classroom Media Inc., 2005)
This program surveys devices used in construction work to connect materials. Nails, screws, bolts, withdrawal strength, clinching, drift bolts, wood screws, skew nailing, nail guns, knuckle plates, nail plates, fixing thin materials, fixing a floor and joining wood to masonry are described
Title from title screen
DVD format
Keywords: Building materials; Woodwork -- Technique; Woodworking tools